Rasch analysis of the University of Washington Self-Efficacy Scale short-form (UW-SES-6) in people with long-standing spinal cord injury. Issue 11 (November 2018) - Post, Marcel; Adriaansen, Jacinthe; Peter, Claudio
Abstract Study design Cross-sectional psychometric study. Objectives The University of Washington Self-Efficacy Scale (UW-SES) is a measure of self-efficacy regarding managing challenges related to multiple sclerosis or spinal cord injury (SCI) that can be used across disabling conditions. The objective of this study was to examine the psychometric properties of its short form, the UW-SES-6, using the Rasch model. Setting Community, The Netherlands. Methods Secondary analysis of data from the ALLRISC study. Participants were 261 individuals with a time since onset of SCI (TSI) for at least 10 years, 18–35 at the onset of SCI, and used a wheelchair in everyday life. Rasch analyses were conducted to examine stochastic ordering (fit), unidimensionality, local dependency, reliability, response scale structure, targeting, and item bias. Results Median age was 47.8 years (Inter-Quartile Range (IQR) 41.9–55), median TSI was 22 years (IQR 16.8–30.3), 73.6% were male, 90.4% had a traumatic SCI, 39.8% had tetraplegia, and 81.6% had motor complete SCI. After merging the middle three response categories of item 4, the UW-SES-6 showed satisfactory item fit without local dependence. The PSI was high (0.87). Comparison of the person and item threshold distributions showed satisfactory targeting of the UW-SES-6 to the study group. No differential item functioning was seen with respect to sex, age, level of education, level and completeness of lesion, and TSI. Conclusions This study showed the UW-SES-6 to be a scale with sound psychometric properties that can be used as a quick and easy self-report measure of self-efficacy in people with SCI.